Detecting ultrafast interatomic electronic processes in media by fluorescence - Knie, André; Hans, Andreas; Förstel, Marko; Hergenhahn, Uwe; Schmidt, Philipp; Reiß, Philipp; Ozga, Christian; Kambs, Benjamin; Trinter, Florian; Voigtsberger, Jörg; Metz, Daniel; Jahnke, Till; et al. (New journal of physics, 2014)
Interatomic coulombic decay (ICD), a radiationless transition in weakly bonded systems, such as solutes or van der Waals bound aggregates, is an effective source for electrons of low kinetic energy. So far, the ICD processes could only be probed in ultra-high vacuum by using electron and/or ion spectroscopy. Here we show that resonant ICD processes can also be detected by measuring the subsequently emitted characteristic fluorescence radiation, which makes their study in dense media possible.
Gesehen am 13.07.2020